Muhammad Shahrur’s Perspective on Gender Equality in Inheritance Distribution - Herianto Putra; Desi Anwar (Indonesian Journal of Islamic Law, 2023)
This research evaluates the dynamics of inheritance distribution in the context of Islamic law (faraid) amidst socio-economic changes and shifting gender roles. Using descriptive qualitative methods, this study explores the views of reformist Mu ḥ ammad Sha ḥ rūr regarding gender equality in the distribution of inheritance, and compares its application in various legal and social contexts. The main findings show that current principles of inheritance distribution are not in line with changing socio-economic realities, in which women have become important economic contributors. This study emphasizes the need for reinterpretation of Islamic heritage norms to better reflect equality and justice, considering individual economic contributions without gender discrimination. Recommendations include legislative reforms that support a more equal distribution of inheritance, increased public education, and the use of ijtihad in legal practice to accommodate contemporary dynamics.